The incidence rate of unresponsive thin endometrium in frozen embryo transfer cycles: A case-series of therapy with granulocyte colony stimulating factor - Shokouhosadat Miralaei; Mahnaz Ashrafi; Arezoo Arabipoor; Zahra Zolfaghari; Saeideh Taghvaei (Shahid Sadoughi University of Medical Sciences, 2019)
Background Treatment-resistant thin endometrium (TTE) during in-vitro fertilization is a relatively uncommon and challenging problem. Objective The primary aim of the study was to assess the TTE rate during frozen embryo transfer (FET) cycles and the secondary aim was to evaluate the effect of intrauterine instillation of granulocyte colony stimulating factor (G-CSF) in these cases. Materials and Methods In this cross-sectional study, all of the women who underwent FET cycles with hormonal endometrial preparation in Royan Institute from June 2015 to March 2018 were evaluated and all of the cases with TTE diagnosis (endometrial thickness < 7 mm after using high doses of estradiol) were included. In the eligible cases, 300 μgr of G-CSF was infused intrauterine. If the endometrium had not reached at least a 7-mm, a second infusion was prescribed within 48 hr later. Results During the study, 8,363 of FET cycles were evaluated and a total of 30 infertile patients (0.35%) with TTE diagnosis were detected. Finally, 20 eligible patients were included. The changes of endometrial thickness after G-CSF therapy were significant (p < 0.001); however, the endometrial thickness did not reach 7 mm in nine patients (45%) and the embryo transfer was canceled. Conclusion It was found that the rate of TTE during the FET cycle is very low and intrauterine perfusion of G-CSF has a potential effect to increase the endometrial thickness in these patients; however, the rate of cancellation was still high and poor pregnancy outcomes were observed.